Emergent open conversion for stent-graft deployment failure in a ruptured thoracic aneurysm - Corinne Kohler, MD; Thomas R. Wyss, MD; Nando Mertineit, MD; Vladimir Makaloski, MD; Juerg Schmidli, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2021)
Thoracic endovascular aortic repair (TEVAR) is the standard of care for ruptured thoracic aortic aneurysms. A 92-year-old man had presented in stable condition but with acute severe back pain. Computed tomography revealed a ruptured thoracic aortic aneurysm. TEVAR (Valiant; Medtronic Vascular, Santa Rosa, Calif) into zone 2 with intentional coverage of the left subclavian artery was planned. After release of the stent-graft body, proximal release of the bare springs was impossible. Troubleshooting techniques were applied; but tip capture could not be released. Emergent conversion to open repair was performed. Intraoperative device deployment failure in TEVAR is rare. The findings from the present report have demonstrated the advantages of having in-house cardiac surgery backup available.